PENYULUHAN KESEHATAN “POLA MAKAN SEHAT UNTUK MENCEGAH COVID-19” DI DESA TRIYAGAN KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Nur Hidayati; Nony Puspawaty; Mardiyono Mardiyono; Soebiyanto Soebiyanto (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
People in rural areas usually have minimal knowledge or information about healthy eating patterns related to nutritionally balanced foods, due to their habits that take it for granted. The increasing number of cases of disease suffered by the community due to unhealthy and inappropriate eating patterns in the selection of food intake for families, especially to deal with this COVID-19 pandemic, it is necessary to provide health education to the community related to healthy eating patterns. As the target audience for the implementation of this service, the community of Triyagan Village, District, Mojolaban, Sukoharjo Regency, includes the stages of preparation, giving pre-test and post-test, presenting material and conducting evaluations. The results of the pre-test and post-test evaluations on knowledge of healthy eating patterns showed a positive direction with an increase in value/score, from an average of 61 to 79 (scale score of 100) after receiving counseling. This evaluation shows that there has been a change in mindset about a healthy lifestyle as an effort to prevent the Covid-19 virus during the pandemic.